PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 25 PADANG - Mardiah, Mira; R.,, Syahrul; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACTÂ There are three research objectives. First, it describes the writing skills of news texts for eighth grade students of SMP Negeri 25 Padang before using the Mind Mapping technique. Second, describing the writing skills of news texts for eighth grade students of SMP Negeri 25 Padang after using the Mind Mapping technique. Third, analyzing the effect of using Mind Mapping techniques on writing text skills for eighth grade students of Padang Negeri 25 Padang.Â Kata kunci: pengaruh, menulis, teknik mind mapping, teks beritaÂ